Hyperbaric prilocaine vs. hyperbaric bupivacaine for spinal anaesthesia in women undergoing elective caesarean section: a comparative randomised double‐blind study. (11th January 2021) - Chapron, K.; Sleth, J.‐C.; Capdevila, X.; Bringuier, S.; Dadure, C.
Summary: Hyperbaric bupivacaine spinal anaesthesia remains the gold standard for elective caesarean section, but the resultant clinical effects can be unpredictable. Hyperbaric prilocaine induces shorter motor block but has not previously been studied in the obstetric spinal anaesthesia setting. We aimed to compare duration of motor block after spinal anaesthesia with prilocaine or bupivacaine during elective caesarean section. In this prospective randomised, double‐blind study, women with uncomplicated pregnancy undergoing elective caesarean section were eligible for inclusion. Exclusion criteria included: patients aged < 18 years; height < 155 cm or > 175 cm; a desire to breastfeed; or a contra‐indication to spinal anaesthesia. Patients were randomly allocated to two groups: the prilocaine group underwent spinal anaesthesia with 60 mg intrathecal prilocaine; and the bupivacaine group received 12.5 mg intrathecal heavy bupivacaine. Both 2.5 µg sufentanil and 100 µg morphine were added to the local anaesthetic agent in both groups. The primary outcome was duration of motor block, which was assessed every 15 min after arriving in the post‐anaesthetic care unit. Maternal haemodynamics, APGAR scores, pain scores, patient satisfaction and side‐effects were recorded. Fifty patients were included, with 25 randomly allocated to each group. Median (IQR [range]) motor block duration was significantly shorter in the prilocaine group, 158 (125–188 [95–249]) vs. 220 (189–250 [89–302]) min, p < 0.001. Median length of stay in the post‐anaesthetic care unit was significantly shorter in the prilocaine group, 135 (120–180 [120–230]) vs. 180 (150–195 [120–240]) min, p = 0.009. There was no difference between groups for: maternal intra‐operative hypotension; APGAR score; umbilical cord blood pH; maternal postoperative pain; and patients' or obstetricians' satisfaction. We conclude that hyperbaric prilocaine induces a shorter and more reliable motor block than hyperbaric bupivacaine for women with uncomplicated pregnancy undergoing elective caesarean section.